Coyuntura Económica - María Carolina Rozo; Avelino Martínez Sandoval; Luz Amelia Vela Enríquez; Holmes Sánchez; Guillermo Aponte (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2009)
Coyuntura económica